Drivers, Challenges, and Impacts of Digital Transformation in the Creative Economy - Muhammad Budi Utama; Fahrul Hudatil Atkiyan; Junaedi Junaedi; Andi Pranata; Ahmad Ahmad (Abdi Masyarakat, 2026)
Digital transformation has significantly influenced the development of the creative economy in the digital era. This study aims to analyze the drivers, challenges, and impacts of digital transformation in the creative economy using a Systematic Literature Review (SLR) approach. Relevant articles published between 2019 and 2025 were collected from reputable academic databases and systematically analyzed. The findings indicate that technological advancement, changing consumer behavior, market competition, and government support are the main drivers of digital transformation in the creative economy. However, several challenges remain, including limited digital literacy, inadequate infrastructure, financial constraints, and data security issues. The study also reveals that digital transformation positively impacts innovation, operational efficiency, market expansion, and business competitiveness within the creative sector. Furthermore, successful digital transformation requires strong human resource capabilities, supportive policies, and sustainable digital ecosystems. This research contributes to the understanding of digital transformation in the creative economy and provides practical implications for policymakers and creative industry practitioners in developing effective digital transformation strategies.